Financing Secondary Education in Kenya: Cost Reduction and Financing Options - Ngware, Moses W.; Onsomu, Eldah N.; Muthaka, David I. (Education Policy Analysis Archives, 2007)
The paper examines the financing status of secondary education in Kenya and explores possible cost reduction and financing options in the long term. Educational needs for secondary education in Kenya are on the increase since the introduction of Free Primary Education in 2003. Financing of secondary education continues to be a challenge to the government, parents and communities at large. Identifying sustainable financing options that maximize on cost-effectiveness in resource utilization is therefore critical. The study utilized secondary data obtained from education trend statistics, the 2003 Kenya school census, and the Teachers Service Commission. The education simulation and financial projection tool provided the basis for projecting both growth in secondary enrollments, resource needs, and financial implications of various policy options. Some of the insights from the study show that expenditure on secondary education as a proportion of GDP and the total education public budget averaged 1.6% and 22%, respectively. Public financing is predominantly recurrent, while non-recurrent expenditures are estimated at 6%. High-income quintiles benefit more from public provision and financing of secondary education compared to the low-income quintiles. Feasible financing options would therefore include increasing secondary education revenue and fiscal allocation on non-salary expenditures. Cost reduction measures should target the expansion of quality day schools, efficiency utilization of teachers, and streamlined procurements. The paper provides research findings and makes objective projections with a view to informing researchers, education managers and policy makers.